1992
DOI: 10.3109/00365529208999945
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cisapride on Relapse of Reflux Oesophagitis, Healed with an Antisecretory Drug

Abstract: Maintenance treatment with cisapride was evaluated in 298 patients in whom reflux oesophagitis had been healed with antisecretory drugs. Initially, 34% of the patients had grade-I oesophagitis, 33% had grade II, and 33% had grade III. The patients were treated with 20 mg cisapride twice daily or placebo for 6 months or until endoscopic relapse was shown if this occurred earlier. Survival analysis showed that cisapride significantly prolonged the time to endoscopic relapse in grade-I patients (P = 0.02). The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 12 publications
3
21
0
1
Order By: Relevance
“…This finding is in agreement with other reports (20), but was not evident as a factor affecting the symptomatic relapse rate in our study. The rate of endoscopic relapse was similar for males and females in all treatment groups.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This finding is in agreement with other reports (20), but was not evident as a factor affecting the symptomatic relapse rate in our study. The rate of endoscopic relapse was similar for males and females in all treatment groups.…”
Section: Discussionsupporting
confidence: 83%
“…The lack of an effect of smoking is counter-intuitive but is found in other reports. Smoking has been found to have no effect on relapse of esophagitis following successful treatment with omeprazole (21) or to be associated with a longer period of remission in patients receiving maintenance therapy with cisapride or placebo (20).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have suggested that relapse is more common in those who are treated with omeprazole, although the exact mechanism remains unclear and there may be confounding factors such as omeprazole only being used in more severe disease. 12,20 It should be noted that proton pump inhibitors have become the treatment of choice in oesophagitis, and so even if the proton pump inhibitor therapy used in this study contributed to the high relapse rate it is simply re¯ecting the relapse rate which will occur in clinical practice. Another reason for treatment failure might be if the drug was not given in an adequate dose and failed to achieve its desired effect.…”
Section: Discussionmentioning
confidence: 99%
“…12±14 In addition, Tytgat et al reported that cisapride reduced any deterioration in quality of life by using a simple visual analogue scale to assess general well-being. 12 A recent combined analysis of two of these studies suggested that cisapride is most effective in patients whose re¯ux symptoms are not refractory to initial treatment with acid-suppressing drugs. 18 This study assessed consecutive patients with a diagnosis of grade II±III oesophagitis who were healed with omeprazole.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also reporting adverse events of cisapride found diarrhoea to be the most common. Tytgat et al [33] found diarrhoea was reported by 9% of the patients taking cisapride and in another study diarrhoea was reported in 4% of cisapride recipients and in 3% of placebo recipients [34] and in 3–6.5% in large non-comparative studies [35, 36, 37], and in a 12-month study by Blum et al [38] diarrhoea occurred in 11 and 4% of cisapride and placebo recipients respectively (p < 0.05). This increased stool frequency during cisapride treatment is not caused by malabsorption of water, fat or bile acids, but seems to be the consequence of a direct motor effect [39].…”
Section: Discussionmentioning
confidence: 99%